Lysolecithin-derived feed additive improves feedlot performance, carcass characteristics, and muscle fatty acid profile of Bos indicus-influenced cattle fed in a tropical environment - Pacheco, Rodrigo Dias Lauritano; Oliveira Gusmão, Jessica; Moura, Gustavo André; Capelari, Matheus; Greco, Leandro; Carvalho, João Carlos Fontanari de; Cervieri, Rafael da Costa; Castro, Patrick André; de Alencar Beserra, Valquíria; Campanelli, Victor Paschoal Consentino; Cabral, Luciano da Silva; Carvalho, Laura Barbosa; et al. (Frontiers in Veterinary Science, 2023)
Lysolecithin might increase ruminal and intestinal emulsification leading to increased digestibility, but there is minimum information about which is the most appropriate phase to start supplementation and its impacts on feedlot performance and muscle fatty acid profile. Two experiments were conducted to evaluate the effects of phase-feeding of Lysoforte™ eXtend (LYSO). In the first experiment, 1,760 predominantly Bos indicus bullocks (initial body weight of 400 ± 0.561 kg) were allocated in a complete randomized block design. LYSO was supplemented at 1g / 1% of ether extract of the diet. Treatments were: no LYSO supplementation (NON); LYSO starting during the growing period and continuing during the finishing period; LYSO starting during the finishing period (FIN); and LYSO during adaptation, growing and finishing periods (ALL). In the second experiment, the same treatments were evaluated, with 96 bullocks (64 Nellore and 32 ½ Nellore × ½ Angus) allocated in a 4 × 2 factorial arrangement (treatments × genotype). For both studies, intake and average daily gain were accessed, carcass characterists were evaluated in the first experiment, while nutrients digestibility and muscle fatty acids profile were measured in the second. In the first experiment, LYSO increased final body weight (P < 0.022) and average daily gain (GRO and FIN; P < 0.05). In the second study, a treatment × breed × feeding phase interaction was observed, with Nellore having a greater average daily gain (P < 0.05) than crossbreds in every phase that LYSO was introduced to the diet. A treatment × feeding phase interaction was observed for digestibility, such that LYSO increased total dry matter (P = 0.004), crude protein (P = 0.043) and NDF (P = 0.001) digestibility during finishing period. A treatment × breed × day classification was observed (P < 0.05). During finishing phase, crossbreds treated with LYSO had greater DMI (P < 0.05) on very hot days than NON. Also, animals treated with LYSO presented greater C18:3 n3 concentration (P = 0.047) in longissimus. Overall, feeding LYSO during GRO and FIN enhanced feedlot performance and should lead to higher intakes during very hot days of the finishing feeding period.